Pendampingan IKM Knalpot Purbalingga dengan Penerapan Green Manufacturing Guna Meningkatkan Kualitas dan Efisiensi Produksi: Pengabdian - Agung Putu Susastriawan, Anak; Setyowati Rahayu, Suparni; Priyambodo, Sigit; Andaka, Ganjar; Sholeh, Muhammad; Marausna, Gaguk (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The small and medium-sized exhaust pipe industry in Purbalingga Regency is one of the region's leading sectors with high economic value, but it still faces obstacles in terms of metal coating and coloring quality. The conventional processes used are generally energy-intensive and produce chemical waste. This community service activity aims to improve the quality of metal plating and coloring on exhaust products through the application of green manufacturing technology based on energy efficiency and environmental friendliness. The methods used in this activity include the application of a green plating system with measured current control and technical training in the use of environmentally friendly plating materials. The results of the activity showed a significant improvement in the quality of the coating, where the gloss level increased by 25%, heat resistance reached 600°C without color change, and corrosion resistance doubled. In addition to improving product quality, this activity also increased the awareness of SME actors of the importance of sustainable production processes in accordance with the principles of green manufacturing.